Tomato potato psyllid (Bactericera cockerelli Sulc) impacts on taewa seed quality and performance preliminary results - Puketapu, A.J.; Gardner-Gee, R. (New Zealand Plant Protection, 2013)
Taewa (Solanum tuberosum L Maori potatoes) are susceptible to tomato potato psyllid (Bactericera cockerelli Sulc TPP) infestation and to infection with the bacterium Candidatus Liberibacter solanacearum (Lso) vectored by the psyllid Current growing systems used by taewa growers leave the crop highly vulnerable to TPP and Lso infection leading to potential reductions in seed tuber quality and harvestable yield Seed tubers for two virusfree taewa lines (Moemoe and Tutaekuri) grown under high (calendar spraying of insecticides) and low (reduced insecticide spray regime) levels of TPP protection in a zebra chip small plot trial during 2011/12 in Pukekohe were stored after harvest Tubers were later sorted into two seed size categories small (